O uso da alfa microglobulina-1 placentária (PAMG-1) no diagnóstico de ruptura prematura de membranas e sua associação com resultados obstétricos e perinatais - Nicolaou, Panait Kosmos (2013)
OBJECTIVE: to study the preditivity of PAMG-1 test for patients with suspected premature rupture of membranes (PROM). METHODS: fifty patients with suspected PROM were selected and allocated them into two groups (25 with PROM and 25 without PROM). All patients were subjected to the PAMG-1 test. The preditivity of PAMG-1 test was evaluated for the time between the exam and birth and days in hospital after delivery. For statistical analysis we used the t test, Mann-Whitney and chi-square. A level of 5% of significance was accepted (p<0,05). RESULTS: the sensitivity, specificity, positive and negative predictive values for the PAMG-1 test were 92%. The rates of false positive and false negative were 8%. The accuracy of the test was found to be 92%. The time between the exam and birth was 29h for patients with positive test and 287,8h for patients with negative test (p=0,0001) and maternal hospitalization was 29h and 130h, respectively (p=0,001). CONCLUSIONS: the PAMG-1 test has high preditivity in suspected cases of premature rupture of amniotic membranes, with low rates of false positive and false negative test results. Moreover, it can reduce the time of maternal hospital stay or avoid maternal hospitalization and thereby reduce public health expenditures.